Perencanaan bantaran sungai bagian hilir Tukad Badung untuk rekreasi di Kota Denpasar - Abdurrahman, Ifham Azhar; Yusiana, Lury Sevita; Utami, Ni Wayan Febriana (Jurnal Arsitektur Lansekap; Vol.5, No.2, Oktober 2019DO - 10.24843/JAL.2019.v05.i02.p01, 2019)
Planning of the tukad Badung downstream riverside for the recreation in the City of Denpasar. River has a very big role for the development of human civilization, that is by providing a source of water for human life and become a common fertilizer located in the valley directly. The flows of Tukad Badung in Denpasar City has the function and potential as a source of irrigation, the source of raw water services, clean water service, drainage, and the future can be used as a recreational water. The purpose of this research is to plan for landscapes that are consistent with those location, and to recommend recreation activities as they can be presented in the landscape of the tukad Badung. The method used in this research is survey with observation, questionnaire, and literature review technique. The results of this research consists of general condition and research site location, inventory, analytical synthesis, conceptual, site planning, and planning of recreational activity. The final result was a site plan of riverside. The conclusion of this research was the physical condition divided by biophysical and social aspects. Concept plan has two stages, basic concepts and development concepts. The recommended activities and recreational facilities which planned were fishing, exercising, picnic, crossing bridges, and taking pictures. It can be suggest that in this research should be considered naturalness and cleanliness of area and create a characteristic at the site